(3JGQjN GdacQ GdGbJUGOj (B/s - (3Ydj, GSeGYjd eMehOs ((3GdGScfOQjI(B: s (3ecJHI GdhaGA GdbGfhfjI(B, s, 2011)
(3GdMGdI GdGbJUGOjI daQfSG bHd GdKhQI h HYOgG, fXGe GdVQGFH h JCNQ GdUfGYI, eMGhdGJ GdGUdGM, GdMGdI GdGbJUGOjI aj CdeGfjG aj ChGFd GdbQf GdJGSY YTQ, GdJLGQI , GdUfGYI h GdRQGYI h JCNQ GdeOf , GdGUdGM aj HQhSjG, GdMGdI GdGbJUGOjI aj GfLdjJQG aj GdbQf GdKGef YTQ, GfJTGQ GdUfGYI h JbOegG hQhGL GdJLGQI GdOGNdjI h GdNGQLjI, GdRQGYI aj ChQHG aj GdbQf GdJGSY YTQ, MdI ChQHG GdRQGYjI bHd GdGfbdGH GdRQGYj h MGdI GfLdjJQG GdRQGYjI HYO GdGfbdGH, GVeMdGd GdRQGYI aj ChQHG h WQb YdGLgG, JbOe GdRQGYI aj aQfSG aj GdbQf GdJGSY YTQ, GdRQGYI aj CdeGfjG aj GdbQf GdJGSY YTQ, fgVI GdRQGYI aj GfLdjJQG , GdKhQI GdUfGYI aj aQfSG , JbOe GdUfGYI aj CdeGfjG, GdYdGbI GdHjFjI GdGfSGfjI, GdfbhO GdOhdjI , GdScGf h GdGfJGL h GdJLGQI , hGbYfG GdGbJUGOj GdYQHj h eDTQGJ COGAGJ GdGbJUGOjGJ GdYQHjI , eDTQGJ GdGfOeGL aj GdGbJUGO GdYGdejs
(3HHdjhZQGajG(B: 435s
Keywords: (3GdEbJUGO(B- (3JGQjNs; (3ChQhHG(B- (3GdEbJUGOs